Market Power and Monetary Policy Transmission - Duval, Romain; Furceri, Davide; Lee, Raphael; M. Tavares, Marina (Washington, D.C. : International Monetary Fund, 2021)
We show that firms' market power dampens the response of their output to monetary policy shocks, using firm-level data for the United States and a large cross-country firm-level dataset for 14 advanced economies. The estimated impact of a firm's markup on its response to a monetary policy shock is large enough to materially affect monetary policy transmission. We also find some evidence that the role of markup in monetary policy transmission, while independent from other channels, is greater for firms whose characteristics - notably size and age - are likely to be associated with greater financial constraints. We rationalize these findings through a simple partial equilibrium model in which borrowing constraints amplify disproportionately low-markup firms' responses to changes in interest rates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Central Banks and Their Policies; Market Structure and Pricing; Monetary Policy; Production, Pricing, and Market Structure; Size Distribution of Firms